2016
DOI: 10.1177/2041669516676823
|View full text |Cite
|
Sign up to set email alerts
|

Back to the USSR: How Colors Might Shape the Political Perception of East versus West

Abstract: People typically process information to confirm their prior held attitudes and stereotypes. As the political relations between NATO and Russia have distinctively drifted apart in recent years, we were interested in how far old-established color depictions referring to the Cold War’s demarcations (USSR = red; NATO = blue) might reinforce people’s political perception of an East versus West antagonism nowadays. Participants received a fabricated news article in which both world powers were either depicted on a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…As in previous research (Gebauer et al, 2016; Palmer & Schloss, 2010; Schloss et al, 2011), political colors have shown their ability to produce consistent behavior. But they have only succeeded in scenarios of uncertainty.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…As in previous research (Gebauer et al, 2016; Palmer & Schloss, 2010; Schloss et al, 2011), political colors have shown their ability to produce consistent behavior. But they have only succeeded in scenarios of uncertainty.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, colors could be a valuable source of knowledge (Graber et al, 2001; Lavin & Lawless, 1998; Shankar et al, 2009) about our political environment. They would be able to activate prior stereotypes (Burkitt et al, 2007; Gebauer et al, 2016; Palmer & Schloss, 2010), and partisan biases that, as shown in several previous researches (Carver, 2001; Lodge & Taber, 2000; Simon et al, 2004; Taber & Lodge, 2006; Westen et al, 2006), and can modify the political behavior of citizens.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Este efecto ha sido ampliamente investigado (cf. Gebauer, Raab, Carbon 2016). Con el acto icónico, estos mecanismos, que parten de la psicología y del encaje social de los receptores, se amplían ahora hasta el punto de que las imágenes se entienden como una fuente de estímulo pseudoviviente que provoca una interacción configurada sistemáticamente: el «acto icónico» supone una interacción entre la imagen y el espectador en la que un impulso esencial emana de la contraparte del receptor.…”
Section: Definicionesunclassified